2012
DOI: 10.1007/s10681-012-0640-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inter-varietal diversity, biotic stresses and environmental productivity on grain yield of spring barley variety mixtures

Abstract: Varietal seed mixtures tend to increase and stabilize crop yields, yet their application is sparse. Large-scale cultivation of variety mixtures may require a better understanding of how inter-varietal interactions and their interaction with the environment may influence the grain yield of variety mixtures relative to their component varieties. For this purpose, six variety mixtures of spring barley and 14 component varieties were grown in each of 17 trial environments. A total of 28 observed and a priori plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…This suggests that crops or varieties with high tillering abilities such as most wheat varieties could benefit more from mixtures of varieties than crops that have a much lower ability for tillering such as maize. Finally, results obtained on barley have already shown that mixing varieties may stabilize production through a better adaptation to environmental variability (Kiaer et al 2012).…”
Section: Potential Sampling Effects In Mixtures Of Varietiesmentioning
confidence: 99%
“…This suggests that crops or varieties with high tillering abilities such as most wheat varieties could benefit more from mixtures of varieties than crops that have a much lower ability for tillering such as maize. Finally, results obtained on barley have already shown that mixing varieties may stabilize production through a better adaptation to environmental variability (Kiaer et al 2012).…”
Section: Potential Sampling Effects In Mixtures Of Varietiesmentioning
confidence: 99%
“…For example, although variation between sites in crop performance is often much greater than variation between cultivars within a site, diverse crop stands comprising several cultivars have not only a similar range of variability within a site but also less variability between sites (Swanston et al . ; Kiær, Skovgaard & Østergard ).…”
Section: Crop Genetic Diversity and Indirect Facilitationmentioning
confidence: 99%
“…The degree of weed interference on the crops depends on the time of weed infestation, on the environment and on characteristics of the weed species (Kiaer et al 2012;Hugo et al 2014).…”
Section: Introductionmentioning
confidence: 99%